Prednisone inhibits osteosarcoma cell by regulating the Wnt/β-catenin signaling pathway - Yo Zhang; Hongmei Zhang; Shanshan Yang; Xiufeng Gao; Wenhao Guo (Bangladesh Journal of Pharmacology)
Prednisone, a synthetic glucocorticoid, possesses a moderate duration of action in the human body. To investigate the effect of prednisone on osteosarcoma cells in vitro, CCK8, wound healing, Transwell assays, flow-cytometry, western blot, and ELISA were used to measure cell proliferation, cell migration, cell invasion, cell cycle, cell apoptosis, and the key proteins in Wnt/β-catenin pathway. The results showed prednisone could inhibit the proliferation in osteosarcoma cells and exhibit lower proliferation toxicity towards normal bone cells compared to cisplatin by 17.5% (p<0.001). Cell apoptosis was increased by 6.6 and 7.4%, cell migration was decreased to 62.6 and –23.9%, G0/G1 phase cells were increased by 33.0 and 17.9%, and S phase cells were reduced by 29.6 and 18.0% (all p<0.001) in Mg63 and Saos-2 cells respectively after prednisone treatment. The expressions of β-catenin, cMYC, cyclin D1, and MMP7 were also reduced. In conclusion, prednisone inhibits osteosarcoma cells by regulating the Wnt/β-catenin signaling pathway.